Análisis del deterioro auditivo en músicos de la ciudad de Quito en función de instrumento interpretado y tiempo de interpretación para el género del rock - Amores García, David Roberto (2015)
This document discusses an application that shows the situation of a musician’s hearing, depending on the instrument interpreted as well as on the years of practice, in order to deliver a predictive tool on the level hearing threshold, for the years that the musician wants to know. To carry this procedure out, audiometric tests were performed to musicians in Quito whose main genre is rock music; complementary acoustic measurements took place where musicians perform their artistic activities, to have a clear vision of what sound levels they are exposed to. This achievement integrated into a single result both values obtained from audiometric tests and values obtained in acoustic measurements. Results show that, in general, rock musicians perform at levels that exceed the established local rules; also, the percentage of people who are knowledgeable about hearing care is relatively low.